INTEGRAÇÃO SENSORIAL EM INTERFACE COM PROCESSO DE INCLUSÃO DA CRIANÇA COM TRANSTORNO DO ESPECTRO AUTISTA EM INSTITUIÇÕES DE EDUCAÇÃO INFANTIL NO MUNICÍPIO DE AÇAILÂNDIA-MA - REIS, Tereza Sabina Souza (2022)
In autism, sensory processing disorders that make up one of the diagnostic criteria bring significant damage to the overall development of this population. This research aimed to analyze the interface between sensory integration and the process of including children with ASD in day care. Based on this ideal, a dialogue was established between the fields of education and neuroscience, specifically the Sensory Integration Theory. Since the difficulties in planning and executing pedagogical practices with these children have been constantly mentioned in teachers' reports. In the methodological design, action research and document analysis were chosen. Through the analysis of the documents, it is inferred that the conceptual construction of disability and autism, as well as the elaboration of public and educational policies aimed at this population, has walked together with changes in paradigms in force at each time, concomitant with scientific studies. On the other hand, with action research, it was possible to perceive the need for acquisition and construction of knowledge that teachers present in relation to school inclusion and that the theoretical support offered by the theory of sensory integration is capable of contributing to the inclusion of the child. with TEA. Therefore, the results were significant in the intentional change in teaching practice, induced by the investigative process of action research, the teachers were instigated to reflect and criticize their own practices, allowing them to broaden their view and open up to the attitudes and experiences of their peers students.